2017
DOI: 10.4314/tjpr.v15i12.31
|View full text |Cite
|
Sign up to set email alerts
|

A review of therapeutic potentials of sweet potato: Pharmacological activities and influence of the cultivar

Abstract: Sweet potato (Ipomoea batatas) is a global food crop, now being recognized as a functional food due to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 46 publications
(36 reference statements)
2
59
1
2
Order By: Relevance
“…I. batatas L., also known as sweet potato with different varieties, is a valuable medicinal plant for the anticancer, antidiabetic, and anti-inflammatory activities in its extract (36,37). In this study, mouse blood biochemistry indicated increased ALT, TG, and TNF-α levels resulting from increased free radical production caused by STZ in diabetic mice; however, these levels were significantly lower in mice who received the WSP-T or WSP-L intervention for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…I. batatas L., also known as sweet potato with different varieties, is a valuable medicinal plant for the anticancer, antidiabetic, and anti-inflammatory activities in its extract (36,37). In this study, mouse blood biochemistry indicated increased ALT, TG, and TNF-α levels resulting from increased free radical production caused by STZ in diabetic mice; however, these levels were significantly lower in mice who received the WSP-T or WSP-L intervention for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive compounds in sweet potato roots, such as phenolics (e.g., chlorogenic, caffeic, and dicaffeoylquinic acids), carotenoids, polysaccharides, and peptides, have generated interest in the field of human nutrition and have renewed the interest of researchers in the agro‐food sector . These compounds are directly responsible for a variety of potential health‐promoting effects exerted by sweet potato roots, including antioxidant, immunomodulatory, anticancer / antitumor, antimicrobial, antiulcer, antidiabetic, antiobesity, and hepatoprotective activities …”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato has gained significant prominence in the past decade owing to its high nutritional value, especially vitamin C, dietary fiber, irons, minerals, provitamin A, carotenoid, bioactive β‐carotene, and phenolic compounds (Lee & Lee, ; Nabubuya, Namutebi, Byaruhanga, Narvhus, & Wicklund, ). Sweet potato is also seen as an important functional and staple food for human consumption due to its high antioxidant, anthocyanin, phytochemicals, immunomodulatory, anticancer, and antimicrobial potentials which are beneficial to human health (Ayeleso, Ramachela, & Mukwevho, ; Tang, Cai, & Xu, ). However, sweet potato is a highly perishable commodity and is difficult to preserve for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato is also seen as an important functional and staple food for human consumption due to its high antioxidant, anthocyanin, phytochemicals, immunomodulatory, anticancer, and antimicrobial potentials which are beneficial to human health (Ayeleso, Ramachela, & Mukwevho, 2017;Tang, Cai, & Xu, 2015). However, sweet potato is a highly perishable commodity and is difficult to preserve for long periods of time.…”
mentioning
confidence: 99%